Analysis of Moral Value in Walt Disney Pictures “Moana” Animated Film - Agustina Indah Bahari; Nilliawaty; Syahrial (Pusat Penerjemah dan Penyunting Universitas Indraprasta PGRI, 2025)
A film is a type of literary work to entertain and convey intended values or messages for the viewers. The purpose of this research was to identify and analyze moral values contained in Disney’s animated film Moana. The researchers focused on this film because it conveys positive moral values and storyline. This research utilized descriptive-qualitative method. This research used the only Moana film as the data source. The data collection for this study consisted of analyzing the film’s script and watching the film in English. The findings showed that Moana performed numerous moral values for the viewers. They are courage, responsibility, self-confidence, self-compassion, hard-working, and helping others. Therefore, the researchers suggests the viewers to not only derive enjoyment from the movie’s plot, but also apply its moral values to enhance their own character to become better individuals.